ROLE AND EFFECT INFLUENCE OF REHABILITATION ELEMENTS IN SPORTS - O.X. Mirzamukhamedov, S.K. Khudaykulov (Galaxy International Interdisciplinary Research Journal, 2022)
Today, in the age of technological progress, when the level of health of the population decreases with a high technical load and insufficient physical activity, the role of physical culture and sports is growing even more. There is no doubt that the rich emotional background sufficiently reduces the level of health and well-being of students, injures their psyche. In Institute for the re-training and professional improvement of specialists in physical education and sport his regard, the search for the most adequate ways and methods to strengthen the psychophysical state of students, the identification of psychological and pedagogical conditions for optimizing this process, the development of health technologies that can reduce the physiological and psychological cost of adaptation and ensure the formation of sustainable attitudes for a healthy lifestyle becomes especially relevant. [9]